The prospective associations among time management tendency, negative emotions, and problematic smartphone use in Chinese nursing students: enlightenment from COVID-19 - Ding, Nani; Shi, Jiaqi; Xu, Huihui; Wang, Xiaoyi; Liu, Guilin; Mao, Lijie; Zhang, Guohua; Zhang, Jingjing (Frontiers in Public Health, 2024)
Purpose The regularity of epidemic prevention and control measures in China has meant that nursing students have been exposed to more electronic devices, while problematic smartphone use has increased. The purpose of this study is to determine the prospective associations among time management tendency, negative emotions, and problematic smartphone use in nursing students during the COVID-19 pandemic. Methods A longitudinal study was conducted between November 2021 and May 2022. A total of 989 nursing students participated. The convenience sampling method was adopted and the following tools were used: the Adolescence Time Management Disposition Scale, the Depression Anxiety Stress Scales – 21, and the Mobile Phone Addiction Index. Multiple parallel mediation models were used by Mplus. Results Time management tendency had a significantly negative effect on problematic smartphone use (p < 0.05). Further tests using mediation models showed that stress as a negative emotion mediated the relationship between time management tendency and problematic smartphone use (p < 0.05) over time. Conclusion Nursing educators need to strengthen the stress resistance and time management ability of nursing students.